STRATEGI PEMASARAN PADA HASIL BUDIDAYA KARANG HIAS Corals DI PT AGUNG AQUATIC MARINE, BADUNG BALI - Wahyuni (Fakultas Hukum dan Ekonomi Bisnis, 2022)
Indonesia is an archipelagic country consisting of 13,466 islands with a land area of ​​1,922,570 km² and a water area of ​​3,257,483 km². Ornamental coral or coral is part of a coral reef ecosystem which is the richest source of marine biodiversity. Ornamental corals can be a source of foreign exchange which can be obtained from diving tourism managers and other marine tourism activities. The purpose of this paper is to analyze the marketing strategy for the cultivation of ornamental corals at PT Agung Aquatic Marine. This writing was prepared based on the results of activities carried out at PT Agung Aquatic Marine, Badung, Bali. The data analysis used is descriptive data analysis. Sources of data used are primary data and secondary data. The type of data used is qualitative data. The data collection methods used are observation, interviews, questionnaires, literature studies, and documentation. The writing results show that the most appropriate marketing strategy to be implemented at PT Agung Aquatic Marine is the SO Strategy (Strength and Opportunities) to improve the quality, stock availability and variety of ornamental coral species. Expanding the market and simplifying distribution channels. Focusing on facility development for sustainable stock availability. Increase promotions by utilizing technological advances.